Nikah Mut'ah Dalam Pandangan Syi'ah - Gourji, Ayatullah Abul Qasim (Sunan Kalijaga State Islamic University & The Asia Foundation, 2002)
In this paper Abul Qasim Gourji highlights several verses or hadith which become the theological base for the legitimacy of mut'sb marriage. As a follower of the Syi' ah School, the writer wishes to clarify the validity of tnut' ah marriage. In his opinion, there is not one verse in the al-Qur'an or the hadith that expresses, either directly or implicitly, a prohibition of mut'ah marriage. By quoting several stories found in the books of Tafsir and laws of the books of Hadith and Tarikh, which all originate from the Sunni school, the writer emphasises that the prohibition on mut' ah marriage was not made by the Prophet, but rather by Umar bin Khattab. And this prohibition, he feels, clearly contradicts the al-Qur'an and the hadith. Moreover, up til now still no agreement has been reached about this prohibition on mut'ahmarriage, which was even practiced by several of the Prophet's companions.